ИССЛЕДОВАНИЕ ПУСКА СИНХРОННОГО ДВИГАТЕЛЯ С ШИРОТНО-ИМПУЛЬСНЫМ ПРЕОБРАЗОВАТЕЛЕМ ЧАСТОТЫ - Синчук , О.Н.; Михайличенко , Д.А. (Інститут електродинаміки НАН України, Київ, 2014)
In the process of the power effective systems development of the synchronous electric motors' start-up it is necessary to solve a problem of the engine’s adequate mathematical model formation in the various systems of coordinates and studying with its help the transfer functions under the various operating influences. This work focuses on the analysis of the transients at the start-up time of the synchronous motor within using the pulse-width converter at trapezoidal, sinusoidal and rectangular output tension on the basis of the mathematical model which is put up in the current stator[1]the stator flux linkage coordinates. References 10, figures 3.